ANALISIS PERUBAHAN FONOLOGIS DALAM PEMBENTUKAN KALIMAH MU’ARRABAH - Muhammad Afif Amrulloh (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2017)
This research aims to know the method of Arabization on Majma ' al-Lugah al-' Arabiyyah Malaky Magazine part 3. Research was carried out using linguistic approach i.e. phonology. The researcher used this type of qualitative research. The research was carried toward the words of Arabization on Majma ' al-Lugah al-' Arabiyyah Malaky Magazine part 3. Data collection was done through documentation technique. This research included library research that takes a data source in the library. The results of this research showed that there were at least three methods of phonological rules used in the Arabization or ta'rib processes. Those three methods were ta'rib process with the changes to the sound, the sound changes and additions, as well as without the changes of the sound.